2014
DOI: 10.1177/0954407014546431
|View full text |Cite
|
Sign up to set email alerts
|

Robust speed synchronization control for clutchless automated manual transmission systems in electric vehicles

Abstract: This paper is concerned with the speed synchronization optimal controller design problem for clutchless automated manual transmission systems in electric vehicles. It is well known that speed synchronization is one of the main challenges in a transmission system. In electric vehicles, clutchless automated manual transmission systems are regarded as promising transmission devices and are generally required to have high-precision speed synchronization capabilities. In order to satisfy this requirement, a robust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 23 publications
0
40
0
Order By: Relevance
“…The state variable is chosen to be x k = [∆ω k m , ω k m ] T and the coefficient matrices of the state space equations are given as Equation (9).…”
Section: Mpc Controller Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The state variable is chosen to be x k = [∆ω k m , ω k m ] T and the coefficient matrices of the state space equations are given as Equation (9).…”
Section: Mpc Controller Designmentioning
confidence: 99%
“…Zhu et al designed a robust speed synchronization control scheme which combined preview control, integral control and state-feedback control together. By employing the H ∞ performance index for investigating and optimizing the controller, the controller design problem is transformed into a linear matrix inequality (LMI) problem [9]. The CLAMT systems in the above study are all applied in electric vehicles, so the transient speed regulation phase is achieved by the electric motor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electric machine modeling Mathematical models of electric machines are well established, the basic dynamics can be captured using equivalent circuit models, as has been performed in [14]. For a three phase permanent magnet DC motor/generator with surface mounted magnets (referred to as EM in Figure 1) the formulation is used to develop a relationship between electrical input and the mechanical output of the motor.…”
Section: 1mentioning
confidence: 99%
“…We refer the readers to [21][22][23][24][25] for some recent work in this area. In addition to the theoretical developments, many experimental studies have demonstrated that the preview control has potential applications in the fields of active suspension systems [26,27], intelligent electric vehicles [28,29], robots [30,31], water tank level control systems [32], brushless DC motors [33], etc.…”
Section: Introductionmentioning
confidence: 99%